The Influence of Intertextuality in the Manuscript Tarjumān al-Mustafīd by Sheikh ‘Abd al-Ra’uf Ali al-Fanshuri al-Jawi - Zainuddin, Zainuddin (El-Sunan: Journal of Hadith and Religious Studies, 2024)
This study examines the intertextual influences in the Quranic exegesis manuscript Tarjumān al-Mustafīd by Sheikh ‘Abd al-Ra’uf Ali al-Fanshuri al-Jawi. By employing an intertextual approach, the research demonstrates that the manuscript is not a mere translation of works by al-Baiḍawi, al-Khazin, or al-Jalālain, as previously assumed. Instead, Tarjumān al-Mustafīd synthesizes and adapts excerpts from these sources alongside others, such as al-Ṡa’labi. Using descriptive-analytical methods and primary manuscripts housed in the Aceh Museum, this study focuses on the exegesis of Surah al-Baqarah to analyze intertextual techniques, including excerpts, parallels, and expansions. The findings reveal that Tarjumān al-Mustafīd integrates intertextual references from multiple tafsir texts while maintaining its originality and independent interpretive framework. This research contributes to a deeper understanding of intertextuality in Quranic exegesis within the Malay-Nusantara tradition.